The 2nd International Online Conference on Polymer Science-Polymers and Nanotechnology for Industry 4.0 - Cicala, Gianluca; Díez-Pascual, Ana; Yusa, Shin-ichi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The field of polymer composites is currently an area of intense research. The 2nd international Online Conference on Polymer Science-Polymers and Nanotechnology for Industry 4.0 was held on 1-15 November 2021. The conference was organized by the open access journal Polymers (MDPI) and offered researchers in the field of polymer and materials science the great opportunity to present their research and exchange ideas. Many works on Advanced Functional Polymeric Materials, Nanotechnologies in Polymer Science, Smart polymeric Synthesis, and Functional Biopolymers were presented.